Két alkotmány (1989 – 2011) Alkotmányos folyamatosság és megszakítottság
Eötvös Károly Institute conference. Speakers: Majtényi László, Tóth Gábor Attila, Miklósi Zoltán, Fleck Zoltán, Hanák András, Körtvélyesi Zsolt, Kis János, Sólyom Péter, Majtényi Balázs.